(untitled) (Journal of Mathematics Mechanics and Computer Science, 2017)
One of the security solutions are detection of intrusion systems based on the anomalous principle. Such systems are usually based on mathematical methods that require a lot of time for preparing statistics. That’s why, a need for more effective methods based on expert approaches. In order to solve this problem, technology is proposed, based on mathematical models and methods of fuzzy logic, and contains eight basic steps (selection of fuzzy data processing method, the choice of method for determining the importance of the factor, the formation of sets of invasions and values, the formation of standards of size, fuzzification values, forming a plurality of critical rules, the definition of initialization matrix formation results), revealing the process of identifying an abnormal condition, generated by a specific type of cyber attacks in the information systems. This technology can be used to create or enhance existing detect systems of cyber attacks on computer networks.